From Transportation Equity to Transportation Justice: Within, Through, and Beyond the State. (November 2020) - Karner, Alex; London, Jonathan; Rowangould, Dana; Manaugh, Kevin
Transportation policies, plans, and projects all flow through state institutions because of the substantial cost of infrastructure and the need to assess transportation system performance, including equity implications. But environmental justice scholarship interrogates the state's role in perpetuating injustice. Most research and planning practice related to transportation equity has relied upon state-sponsored analytical methods. Transportation planners and scholars can benefit from critical assessments of these approaches. We propose a shift in focus from transportation equity to a broader consideration of transportation justice that is more closely aligned with models of social change promulgated in the environmental justice literature and by related movements.